MAINTENANCE KERUSAKAN CHECK VALVE POMPA DRAINAGE PUMP - Ariska Purnama; Yovan Witanto; Afdhal Kurniawan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
A drainage pump function is to pump water from the sump pit to the tail race. The drainage pump has a check valve to operate optimally. A check valve is a type of valve used in a piping system to prevent backflow, contamination between fluids, and isolating low-pressure areas or systems from high-pressure ones. One of the problems is the occurrence of blockages which result in damage to the check valve on the drainage pump. The purpose of this obsevation is to be able to find out the corrective maintenance process on the check valve in the Tes's Hydroelectric Power Plant, and to find out the effect of check valve damage on the reduction of electric power in the Hydroelectric Power Plant generator unit. At the time before maintenance was carried out on the check valve of the drainage pump, it made a decrease in electric power, thus corrective maintenance was carried out on the check valve on the drainage pump to maximize the electric power from the generator unit.